Potential health benefits of phenolic compounds in grape processing by-products - Averilla, Janice N.; Oh, Jisun; Kim, Hyo Jung; Kim, Jae Sik; Kim, Jong-Sang (Food science and biotechnology, 2019)
Prevention emerges as a powerful approach in minimizing the risk of deleterious lifestyle diseases because therapies do not necessarily guarantee a permanent cure. Accordingly, consumers’ growing preference for natural and health-promoting dietary options that are rich in antioxidants has become widespread. Grape ( Vitis vinifera ) is an antioxidant-rich fruit extensively grown for fresh or processed consumption. The long-term consumption of its polyphenolic antioxidants may promote multiple health benefits. However, grape pomace (GP), consisting of peel, seed, stem, and pulp, is discarded during grape processing, including juice extraction and winemaking, despite its substantial antioxidant content. Polyphenolic extraction techniques have been widely explored to date, but the consolidation of reported physiological impacts of GP-derived polyphenolic constituents is limited. Thus, this review highlights current studies of the potential applications of GP extract in disease prevention and treatment, emphasizing the major influence of polyphenolic compositions and origins of different grape varieties.